Synthesis of Spiro Barbiturates and Meldrum’s Acid Derivatives via a [2+2+2] Cyclotrimerization - Kotha, Sambasivarao; Sreevani, Gaddamedi (Synthesis, 2018)
Intermolecular [2+2+2] cycloaddition of propargyl halides with 1,6-diynes was accomplished with a catalytic amount of Mo(CO)6 to generate benzyl halo barbiturates and Meldrum’s acid derivatives containing a spiro linkage. Furthermore, we have extended this methodology to synthesize linearly fused Meldrum’s acid derivatives via Diels–Alder reaction using rongalite chemistry.
Keywords: barbituric acid; Meldrum’s acid; [2+2+2] cycloaddition; Mo(CO)6; spirocycles; benzyl halides; Diels–Alder